The Ijon System in Livestock Trading as an Economic Driver for the Sasak Community: A Socio-Legal Study in Gelanggang Village, East Sakra District, East Lombok Regency - Masyhur (Faculty of Law, University of Mataram, 2026)
The purpose of this research is to determine the implementation of ijon (pawn-purchase) trading within the Sasak indigenous community of Lombok and to analyze the legal protection regarding such practices. The research method employed is a normative-empirical approach, utilizing several methods: the statute approach, case approach, and conceptual approach. The results of this study indicate that: First, the ijon system in Lombok is a traditional pledging system involving the exchange of assets for a promise of future payment at a higher value. This system emerged as an alternative for people with limited access to formal financial institutions. Beyond meeting urgent financial needs, ijon also possesses a business dimension where the lender profits from the price difference. Second, the practice of the ijon system strongly contradicts universally applicable legal principles. Despite being a customary practice among the Sasak people in Gelanggang Village, East Lombok, transactions using the ijon system are legally declared invalid and have the potential to disadvantage one of the parties involved. This is because the system does not meet the requirements for a valid agreement.This reseach aim to find out the implementation of ijon (pawn-sale) trading in Sasak lombok indiginous community and to determine legal protection for ijon (pawn-sale) trading. This reseach use normative empirical method with statute aprroach, conceptual approach and case approach. The result of this studi find that: first, ijon system in Lombok is a traditional pawn system which involves an asset exchanges with a promise of a higher repayment in the future. This sytem arise as an alternative for society member who has limited acces to formal finance institution. In addition to fullfill urgent financial needs, ijon also has business dimension in which the lender derives profit from the price difference. Second, ijon system practice contrary to the universal legal principles. Eventhough, this sytem already become Sasak comunity customary in Gelanggang Village, East Lombok, under the law, ijon transaction may declare invalid and may potentially cause harm to one of the parties involved. This is due to the sytem does not satisfy the requirement of a valid agreement.